Feasibility and acceptability of peer‐delivered HIV and syphilis self‐test kits and assisted partner notification services for gay, bisexual and other men who have sex with men: a qualitative study in Uganda - Stephen Okoboi; Andrew Mujugira; Deborah Ekusai‐Sebatta; Adeline Twimukye; Peninah Tumuhimbise; Brian Aliganyira; Barbara Castelnuovo; Rachel King (Journal of the International AIDS Society)
Abstract Introduction There is a need to combine different approaches to tackle the HIV epidemic, particularly in high‐incidence populations. We explored the feasibility and acceptability of using peer‐delivered HIV self‐testing (HIVST), syphilis self‐testing (SST) and assisted partner notification (APN) services among gay, bisexual and other men who have sex with men (GBMSM) in Uganda. Methods From November 2023 to March 2024, we conducted in‐depth interviews with 20 purposively selected GBMSM peers and 10 healthcare workers (HCWs). The GBMSM and HCWs interviews explored their perspectives on (1) the feasibility, acceptability and preferences for peer‐delivered interventions (HIVST, SST and APN) and (2) strategies and methods of reaching individuals who had not been tested or tested more than 6 months before the interview. We used a content analysis approach to define and organize codes deductively and inductively to identify themes. Results The median age of the 20 GBMSM peers was 27 years (interquartile range [IQR], 22–35 years), and 37 years (IQR, 25–52) for the 10 HCWs, of whom seven were female. We identified four emerging categories: (1) Trust: GBMSM peers and HCWs expressed trust in the peer delivery of self‐test kits (HIVST and SST) to obtain same‐day results effectively. HCWs were preferred over peers for APN services in reaching sexual contacts of index clients for testing; (2) Intimate partner violence (IPV): Although initial concerns about IPV were raised concerning both HIVST programmes and peer APN strategies, such incidents were rarely reported in practice; (3) Entry point: Similar to HIVST, SST was a self‐administered activity that served as an entry point for HIV testing discussions among GBMSM who had either never undergone or had postponed testing. Self‐test kits could also facilitate pre‐sexual testing among GBMSM; (4) Social media: Campaigns on social media dedicated to promoting self‐testing could expand testing coverage services to GBMSM vulnerable to HIV and syphilis acquisition. Conclusions HCWs and GBMSM peers preferred delivery of self‐test kits through peers over facility‐based approaches; however, they favoured HCWs for providing APN services. Integrating peer‐delivered self‐testing programmes into differentiated testing models and leveraging social media influencers could expand testing coverage among GBMSM.